Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Produktivitas Karyawan pada Badan Penghubung Pemerintahan Provinsi Kalimantan Timur di Jakarta - Agung Ahmad Saputra; Tungga Buana Irfana; Tungga Buana Diana (Universitas 45 Surabaya, 2024)
Human resources determined by the organization that has been given a positive contribution to all agency activities in achieving its goals, then each employee is expected to have high work motivation so as to increase high employee productivity. Motivation is very important by management if government agencies expect every employee to be able to make a positive contribution to the achievement that has been determined so that without motivation to work for the benefit of the agency so that the goals that have been set will not be achieved.